Development of Interactive Learning Media Based on Powerpoint and Desmos Applications For Curved Surface Solid Geometry - Mentari Sukma, Mentari; Purba, Fernando; Tarigan, Nafa Cleo Wulandari; Sihombing, Thresia Veronika; Suwanto, Fevi Rahmawati (Insitut Agama Islam Negeri Kerinci, 2024)
This study aims to develop interactive learning media based on PowerPoint and Desmos applications for studying curved surface solid geometry. The approach used is Research and Development (R&D), focusing on data collection through questionnaires to measure the effectiveness of the developed media. Three validators were involved in the validation process to ensure the accuracy and validity of the content and instructional media structure. Subsequently, the media was piloted with 10 tenth-grade students from SMA Negeri 1 as part of evaluating its practicality and ease of understanding. The research findings indicate that the interactive PowerPoint-based learning media and Desmos application developed by the researcher meet highly valid criteria. Validation by three independent validators confirms that the content and presentation of the media align with expected standards. Furthermore, student feedback during the pilot study indicates that the media is perceived as practical and easy to comprehend, facilitating the teaching and learning process more effectively. Thus, this development of learning media contributes positively to enhancing the quality of learning curved surface solid geometry through the integration of relevant and innovative technologies.